Integrating Digital Literacy into Writing Instruction: Enhancing Student Engagement and Proficiency - Satya Narayan (JEIT (Journal of Educational Innovations and Technologies), 2025)
Digital literacy has become an essential competency in the 21st century, intersecting with various domains of education, yet its integration into writing instruction remains underexplored. Addressing this gap, the study investigates the impact of embedding digital literacy practices into writing courses at Maharishi University of Information Technology (MUIT). The goal is to enhance students' writing performance and equip them with skills for academic and professional success. Using a quasi-experimental design, the study involved 60 undergraduate students, equally divided into experimental and control groups. Participants were selected through purposive sampling to ensure comparable baseline writing skills. Data were collected over eight weeks using standardized writing tests and a rubric-based digital literacy assessment. The experimental group received digital literacy-integrated instruction, utilizing tools like Google Docs, Grammarly, and Turnitin, while the control group followed traditional methods. Descriptive and inferential statistical methods were applied for data analysis. The experimental group demonstrated significant improvements in coherence, organization, and engagement in writing compared to the control group. Cohen’s d indicated a large effect size, affirming the efficacy of digital literacy integration. Findings underscore the transformative potential of digital tools in enhancing student writing proficiency and engagement. However, challenges such as the digital divide and faculty readiness persist. These results have critical implications for policy and practice, advocating for professional development programs and equitable resource distribution. Future studies should explore long-term impacts and strategies for overcoming barriers to digital literacy integration.